Penerapan Metode ADDIE dalam Membangun Sistem Informasi Manajemen Aset Berbasis Web pada Unit Kerja Khusus Pusat Pengembangan Kedokteran Indonesia - Akrom, Mohamad Akromudin; Munggaran, Lulu Chaerani (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Special Work Unit of the Indonesian Medical Development Centre (UKK PUSBANGKI) has a problem in managing its assets, where 30% of data processing uses a semi-computerised system and the remaining 70% manually, so it has the potential to suffer losses for the loss of its assets. The purpose of this research is to design a website-based asset management information system so that asset management can be integrated properly. The method used in this research uses the ADDIE method (Analysis, Design, Development, Implementation, Evaluation) with a systematic and structured approach in designing the programme. The web-based asset management application is built using Bootstrap 3 on the front-end (HTML, CSS, Javascript) which has advantages in terms of website appearance with responsive design and can be customised according to end-user needs. In addition, the use of XAMPP (Apache, MySQL, PHP) and Unified Modeling Language (UML) simultaneously can increase efficiency in the process of developing and producing reliable and secure applications. Based on the results of implementation and evaluation, it can be concluded that the web-based asset management information system has succeeded in increasing 90% time and cost efficiency in tracking assets, as well as 95% effectiveness in reducing incidents of asset loss, so that the work of the asset management unit at UKK PUSBANGKI can be carried out properly, quickly and integrated.